2022
DOI: 10.3389/fimmu.2022.908693
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Airway Inflammation in Lung Allografts

Abstract: Lung transplant remains a key therapeutic option for patients with end stage lung disease but short- and long-term survival lag other solid organ transplants. Early ischemia-reperfusion injury in the form of primary graft dysfunction (PGD) and acute cellular rejection are risk factors for chronic lung allograft dysfunction (CLAD), a syndrome of airway and parenchymal fibrosis that is the major barrier to long term survival. An increasing body of research suggests lymphocytic airway inflammation plays a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 174 publications
0
6
0
Order By: Relevance
“… 17 As described earlier, Lymphocytic airway inflammation was indeed previously proposed as a major driver of CLAD. 18 Mucus plugs were often found, mostly in the vicinity of CB lesions, and were filled with neutrophils and some eosinophils, also being related to neutrophils in the airway wall. Interestingly, BOS is predominantly characterized by neutrophilic airway inflammation, mainly shown on BAL, possibly being related to infectious episodes.…”
Section: Discussionmentioning
confidence: 99%
“… 17 As described earlier, Lymphocytic airway inflammation was indeed previously proposed as a major driver of CLAD. 18 Mucus plugs were often found, mostly in the vicinity of CB lesions, and were filled with neutrophils and some eosinophils, also being related to neutrophils in the airway wall. Interestingly, BOS is predominantly characterized by neutrophilic airway inflammation, mainly shown on BAL, possibly being related to infectious episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Risks factor associated with development of CLAD are lymphocytic airway disease (LAD), B-grade (lymphocytic bronchitis) and E-grade of acute cellular injection (ACR). 23 Macrolides is a class of antibiotics, including azithromycin and clarithromycin. These have often been used for treatment in post-lung transplant patients who developed CLAD.…”
Section: Effect Of Air Pollutions On Postoperative Respiratory Outcomesmentioning
confidence: 99%
“…Clinical syndrome of CLAD can be described as: 1) bronchiolitis obliterans (BOS) (obstructive pattern) or 2) restrictive allograft syndrome (RAS). Risks factor associated with development of CLAD are lymphocytic airway disease (LAD), B‐grade (lymphocytic bronchitis) and E‐grade of acute cellular injection (ACR) 23 . Macrolides is a class of antibiotics, including azithromycin and clarithromycin.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous syndrome of lymphocytic bronchitis has been identified as a precursor and risk factor for CLAD, associated with BAL neutrophils, and reversal following AZI treatment. [7][8][9] A CLAD prevention study of 83 LTx recipients randomized to AZI or placebo at hospital discharge found decreased BAL neutrophils, improved FEV 1 , and better CLAD-free survival in Background. Large-airway lymphocytic inflammation (LB), assessed on endobronchial biopsies, has been associated with acute cellular rejection and chronic lung allograft dysfunction (CLAD).…”
mentioning
confidence: 99%
“…An analogous syndrome of lymphocytic bronchitis has been identified as a precursor and risk factor for CLAD, associated with BAL neutrophils, and reversal following AZI treatment. 7-9…”
mentioning
confidence: 99%